Improving of learning outcomes in greatest common divisor and lowest common multiple mater by developed safari numbered model - Safari, Ibnu Wahid; Darwis, Muhammad; Kurnia, Adi; Basuki, Rahmat (Universitas Islam Negeri Raden Intan Lampung, 2023)
The purpose of this study was to determine the improvement in learning outcomes of the Greatest Common Divisor (GCD) and Lowest Common Multiple (LCM) by developing the Safari Numbered Model (SNM). Further, the activeness of students was also measured. The method used in this study was a quasi-experimental. Data collection was carried out using a test instrument to obtain students' mathematics learning outcomes and a questionnaire to measure the activeness of the students. Data analysis is carried out using the Kolmogorov-Smirnov (KS) test and a two-way ANOVA statistical test. Based on the results of the research, it can be concluded that the implementation of SNM can improve the learning outcomes in GCD and LCM. But the student’s activeness does not affect learning outcomes because the student has been active since the beginning of the lesson.